Production of bioethanol from cassava starch via separate hydrolysis and fermentation - Choo, Boon Chong (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Nowadays bioethanol is being used extensively in fuel production. Therefore it is very important to investigate any cost-effective bioprocessing that can improve the overall production yield and cost. The aim of this study was to produce bioethanol from cassava starch by Kluyveromyces marxianus at a laboratory scale and also a 5L fermentation rig. To produce bioethanol in large volumes at an affordable price, a separate hydrolysis and fermentation (SHF) process of cassava starch was introduced due to high sugar content in the starch using thermoanaerobe which could reduce the cooling time after hydrolysis. A combination of 0.35% v/w amylase and 0.20% v/w amyloglucosidase proved to be the best in the hydrolysis of cassava starch with 19.18 g/L of sugar produced. A 15 g/L of K. marxianus showed to be the best yeast concentration which could produce the highest bioethanol, 42.85 g/L. When the laboratory scale was scaled up to 5 L fermentation, the result was comparable, 42.33 g/L. The same SHF parameters in laboratory scale had proven to be effective in a larger scale fermentation as it showed similar results.